Curriculum Financing in Basic School Education in Nigeria - Adamu, Zakari; Mohammed, Ahmed; AYOKO, Victor Olugbenga (Researchparks Publishing, 2023)
This paper discussed the challenges facing curriculum financing in Basic Schools Education in Nigeria. Secondary data obtained from print and online publications were used for the paper. The paper concluded that poor implementation of national policy on education financing, poor access to counterpart funding, insecurity problems, corruption, subsidy payment, state and national debt servicing, poor private contributions and fall in national revenue are challenges hindering effective curriculum financing in the Basic school education in Nigeria. Based on these challenges, the paper hereby suggested the following; that federal , state and local governments should develop the political will to implement the national policy on funding education in Nigeria. The government should use its anti-corruption agencies to fight all forms of corruption in the administration and management of Basic Education. The government should stop the subsidy payment regime and reinvest the funds into critical sectors like health and education with special consideration to Basic education.